American Grand Strategy and National Security - Clarke, Michael. author. aut Link
XII, 570 p. 1 illus.
Keywords: This book explains the grand strategic behavior of the United States from the Founding of the Republic to the Trump administration. To do so, it employs a neoclassical realist framework to argue that, while systemic change explains the broad evolution of US grand strategy, the precise shape and content of the grand strategies pursued has been conditioned by domestic political culture and interests. The book argues that distinct political cultures of statecraft (Hamiltonian, Jeffersonian, Jacksonian, and Wilsonian) have acted as permissive filters through which policy-makers have interpreted and responded to systemic stimuli, making some grand strategy choices more likely than others in the pursuit of national security. In particular, this book demonstrates that the American pursuit of primacy was facilitated by the predominance from the mid-19th century onward of the extroverted and vindicationist Hamiltonian and Wilsonian forms of statecraft, which reached a peak of influence at the end of the Cold War. The grand strategic overreach of the George W. Bush administration, however, stimulated the resurgence of the long dormant, introverted, and exemplarist Jeffersonian and Jacksonian forms of statecraft under the Obama and Trump administrations, respectively resulting in grand strategies of “decline management” and decline "denial." Ultimately, the return of exemplarist sentiment suggests a breakdown in elite consensus about the nature and purpose of American power in the 21st century. Dr. Michael Clarke is Senior Fellow at the Centre for Defence Research, Australian Defence College, and Visiting Fellow at the Australia-China Relations Institute, University of Technology Sydney, Australia.